Parents’ Perception on Verbal Abuse to Early Childhood: A Case Study - Izzul Fitriyah; Akbar, Sa’dun; Rasyad; Redjeki , Endang Sri (International Journal of Psychosocial Rehabilitation, 2020)
Violence against early childhood is still an interesting issue to study, especially verbal violence that often often occurs in daily life. Verbal violence has an equally terrible impact on mental and character development in early childhood. The purpose of this study was to determine the perceptions of parents about verbal violence committed to early childhood. This study uses a qualitative approach with a focus on phenomenological studies. The population and sample in this study are parents who have children aged 3-6 years located in Sidoarjo City, participants in this study amounted to 4 people. The data collection process was carried out using in-depth interview techniques to the research participants. 50% of study participants stated that verbal violence is an expression of words that should not be spoken. All participants know and understand this is a form of verbal violence, but this still continues to happen, and research participants assume verbal abuse on children has an impact that is no more severe than physical violence.